G190(P) Patient and family experience of endoscopy at a tertiary paediatric gastroenterology unit. (24th May 2017) - Wan, JWY; Griffiths, E; Thomson, M; Campbell, D; Urs, A; Belsha, D; Rao, P; Narula, P
Abstract : Background: A paediatric global ratings scale for endoscopy(PGRS) is currently being piloted and this will provide a quality and safety framework for service improvement in Paediatric endoscopy units. An important aspect of this is patient involvement and an annual survey on the patient's experience. Aim: A patient/parent feedback survey was used to evaluate the endoscopy experience for our patients and family, as part of an annual endoscopy audit plan. Method: A questionnaire that has previously been approved by our clinical governance team in 2013 was used. Questionnaires were distributed to patients and parents over a 3 week period (24/10/16–11/11/16). Results: 28 questionnaires were returned, including an even spread between age groups. The results are illustrated in Table 1 . Conclusion: Overall, patients and families have had a good experience of endoscopy at our Unit, which is in line with previous studies. Areas for improvement include a need for specific endoscopy information and post procedure advice leaflets, and adolescent care.